Fast-Track and Integration-Free Method of Genome Editing by CRISPR/Cas9 in Murine Pluripotent Stem Cells - Mamun, Md Mahfuz Al; Bukhari, Ihtisham (Frontiers in Cell and Developmental Biology, 2022)
CRISPR/Cas9 system has unprecedentedly revolutionized genome editing technology, which is being successfully applied virtually in all branches of the biological sciences. Although much success has been attained in gene manipulation, still the majority of methods are laborious, non-integration-free, and require prolonged time for the expansion of mutant cells pools/clones while fewer cells exhibit functional knockout efficiency. To overcome these obstacles, here, we describe an efficient, inexpensive, integration-free and rapid one-step protocol for CRISPR/Cas9-assisted gene knockout in murine pluripotent stem cells (PSCs). Our protocol has streamlined both the liposome-based transfection system and screening strategy to work more efficiently with small numbers of PSCs (~2.0x104 cells) and to minimize the laborious steps of lentiviral packaging, transduction, and single clone passaging. In our method, around 90% (CI=95%, 79.5230%-100%) of PSC colonies harbored functional knockout in the context of protein expression. Therefore, the current protocol is technically feasible, time-saving and highly efficient for genome editing in pluripotent stem cells.